2018
DOI: 10.3390/met8110965
|View full text |Cite
|
Sign up to set email alerts
|

Probability-Statistical Estimation Method of Feed Influence on As-Turned Finish of Steels and Non-Ferrous Metals

Abstract: Based on the experimental data on the roughness parameter Ra, which stands for the mean arithmetic deviation of the profile, as obtained in the process of turning test specimens from different materials with constant elements of the cutting mode (depth a and velocity v) and structural-geometric parameters of the cutting tool, but with different feed rates f, the probability-statistical method for estimating the influence of feed rate f on the resulting surface roughness by the parameter Ra is proposed using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Machining plays an important role in converting raw material to a desired shape by metal removal in the form of chips. Lot of heat is generated near tool and workpiece [1,2] interface due to the development of friction between them, where cutting fluids are employed to overcome this effect [3]. Lubrication plays a vital role in cooling tool and work piece and flushing the chips away from the machining area, machining performance of vegetable based coolants compared to conventional coolants have improved thermal conductivity in maintaining the cutting temperature during machining, between the workpiece and tool interface and also reduces the ecological problems associated with the enviroinment [4].…”
Section: Introductionmentioning
confidence: 99%
“…Machining plays an important role in converting raw material to a desired shape by metal removal in the form of chips. Lot of heat is generated near tool and workpiece [1,2] interface due to the development of friction between them, where cutting fluids are employed to overcome this effect [3]. Lubrication plays a vital role in cooling tool and work piece and flushing the chips away from the machining area, machining performance of vegetable based coolants compared to conventional coolants have improved thermal conductivity in maintaining the cutting temperature during machining, between the workpiece and tool interface and also reduces the ecological problems associated with the enviroinment [4].…”
Section: Introductionmentioning
confidence: 99%
“…A statistical method to estimate the influence of cutting parameters on surface roughness in turning operations of several alloys of the Fe-C class and non-ferrous metals was proposed in [ 25 ]. Analytical and empirical relations describing the dependence of surface roughness in relation to feed rate were achieved and showed that the already well-known analytical relations of cutting parameters in the literature cannot always adequately describe the experimental data.…”
Section: Introductionmentioning
confidence: 99%